Distress symptoms and alcohol consumption: anxiety differentially mediates drinking across gender - Torres, Oscar V.; Estep, Justin C.; Gwin, Mary; Aramovich, Nicholas P.; Thomas, Giovanni; Villalta, Lan (Frontiers in Psychology, 2023)
Introduction The consumption of alcohol remains a significant health concern and represents a prevalent form of substance use worldwide. Previous research has identified sex differences in the consumption of alcohol. This study explores the relationship between drinking and the presence of distress symptoms across gender. Based on previous research, it was hypothesized that presence of distress symptoms, defined as increases in anxiety and depression, would be prominent features associated with alcohol consumption among women compared to men. Methods A sample of undergraduate students (N = 448) participated in an online-based questionnaire (71% female; M age = 22.1; 42.9% Hispanic/Latino). The questionnaire contained assessments related to demographic information and alcohol consumption over the past 30 days. Anxiety and depression symptoms were assessed using the Hospital Anxiety and Depression Scale. Results Gender differences were observed with men consuming more alcoholic drinks than women. However, women who consumed alcohol reported having more distress symptoms relative to their male counterparts. A logistic regression revealed that this gender difference was moderated by anxiety, such that greater anxiety scores associates with whether women consumed alcohol. However, an ordinary least squares regression revealed that for men, anxiety scores significantly related to the amount of drinks consumed. Gender differences were not detected in relation to alcohol consumption and depression. Conclusion Our findings contribute to the literature by indicating that the mere presence of distress symptoms reveals distinctive gender-specific differences in relation to alcohol consumption in a non-clinical population. Identifying the distinct associations linked with alcohol use for men and women can aid in reducing drinking disparities among young adults.